GC-MS Compositional Analysis of Essential Oil of Leaf and Fruit Rind of Citrus maxima (Burm.) Merr. from Coastal Karnataka, India - D. Anupama Prasad, B. Rajendra Prasad, D. Krishna Prasad, Puneeth Shetty, K. N. Sunil Kumar (Journal of Applied Pharmaceutical Science, 2016)
Essential oils derived from plants by hydro distillation possess several medicinal properties. Citrus maxima (Burm.) Merr. fruit is nutritive, cardiotonic, refrigerant, in stomach troubles, puerperal sepsis and insanity; while leaves are useful in epilepsy, chorea, convulsive cough and stomach pain due to indigestion. Gas chromatography coupled with mass spectroscopy (GCMS) has been used for detection and identification of volatile components from the hydro-distillate from leaf and rind of Citrus maxima (Burm.) Merr. of Rutaceae. Yield of oil was more in rind (0.12%) compared to leaf (0.07%). Forty two and thirty four compounds were detected from leaf and fruit respectively, among which citronellol (28.26%) was the major component in the leaves while D-limonene (89.04%) in the rind. Volatile compounds responsible for various medicinal properties are identified from hydro-distillate of Citrus maxima (Burm.) Merr. from Dakshina Kannada using GC-MS.
Keywords: Citronellol, essential oil, GCMS, herbal medicine, hydro-distillation, limonene.